Validity and reliability of critical speed, critical stroke rate, and anaerobic capacity in relation to front crawl swimming performances - Dekerle, J.; Sidney, M.; Hespel, J. M.; Pelayo, P. (International Journal of Sports Medicine, 2002)
Abstract.The purpose of this investigation was to determine whether the concepts of critical swimming speed, critical stroke rate and anaerobic swimming capacity could be used by coaches as a reliable index in order to monitor endurance performances in competitive swimmers. The results of this study conducted with well-trained swimmers showed that the 30-min test velocity (V30) is not different from the critical swimming speed determined from 200- and 400-m tests but is overestimated by 3.2 %. Furthermore, a regression analysis of the number of stroke cycles on time calculated for each swimmer showed a linear relationship (r(2) greater than 0.99 and p less than 0.01). The 30-min stroke rate test (SR30) was not different from the critical stroke rate determined from 200- and 400-m tests after a correction of minus 3.9 %. These data suggest that the slope of this regression line represents the critical stroke rate defined as the maximal stroke rate value, which can theoretically be maintained continuously without exhaustion. Coaches could easily use critical swimming speed combined with critical stroke rate in order not only to set aerobic training loads but also to control the swimming technique during training. Besides, anaerobic swimming capacity (ASC) values defined as the y-intercept of the regression line between distance and time were not correlated (p > 0.05) with the determined distance over which a significant drop in the maximal speed could be noticed on a 25-m test. Thus, ASC does not provide a reliable estimation of the anaerobic capacity.